The therapeutic advantage of combination antihypertensive drug therapy using amlodipine and irbesartan in hypertensive patients: Analysis of the post-marketing survey data from PARTNER (Practical combination therapy of Amlodin and angiotensin II Receptor blocker; safety and efficacy in patients with hypertension) study. (3rd October 2015) - Ishimitsu, Toshihiko; Fukuda, Hirofumi; Uchida, Masako; Ishibashi, Kazushi; Sato, Fusako; Nukui, Kazuhiko; Nagao, Munehiko
Abstract: Two-thirds of hypertensive patients need a combination antihypertensive therapy to achieve the target blood pressure (BP). The PARTNER (Practical combination therapy of Amlodin and angiotensin II Receptor blocker; Safety and efficacy in paTieNts with hypERtension) study is a prospective specific clinical use survey examining the efficacy and safety of 12-week treatment with amlodipine (AML) and Angiotensin II Receptor Blocker (ARB) in 5900 hypertensive patients. The current analysis was performed as to the BP control, adverse reactions, and the effects on laboratory data in patients treated with the combination of AML and irbesartan (IRB), namely the patients added AML to already taking IRB (AML add-on group, n  = 1202) and the patients added IRB to AML (IRB add-on group, n  = 1050). Both study groups showed distinct decreases in office BP at 4 week ( p  < 0.001) and the antihypertensive effects were sustained to 12 week ( p  < 0.001). The percentage of patients achieving BP < 140/90 mmHg was ∼70% in either group. Proteinuria and estimated glomerular filtration rate (eGFR) were significantly improved in hypertensive patients with baseline eGFR <60 ml/min/1.73 m 2 . Serum uric acid was reduced either by adding AML or IRB, and the reductions were prominent in patients with serum uric acid >7 mg/dl. The incidence of adverse reactions was as few as 1.11% and there were no severe adverse reactions which hampered the continuation of combination therapy. In conclusion, combination antihypertensive therapy with AML and IRB effectively lowers BP without particular safety problems, reduces serum uric acid especially in patients with hyperuricemia and exhibits renoprotective effects in patients with chronic kidney disease.